An experimental study on effects of wheatgrass (Triticum aestivum) juice on low density lipoprotien (LDL) level in blood of experimentally induced hypercholesterolaemic male long Evans rat (Bangladesh Journal of Physiology and Pharmacology, 2015)
An experimental study was done to observe the hypocholesterolaemic effect of wheatgrass (Triticum aestivum) juice on experimentally induced hypercholesterolaemic rats, especially on serum low density lipoprotein (LDL) level, which was carried out in the Department of Pharmacology & Therapeutics, Dhaka Medical College, Dhaka, between July, 2009 and June, 2010. A total number of 48 healthy adult male Long Evans rats (Norwegian strain) were used for the present study. 6 rats were taken in each group of total 8 groups treated differently with 1 control group. Rats of the first 5 groups were sacrificed at 29th day and their serum total cholesterol levels were measured. The rest of the rats were sacrificed at 57th day and their serum total cholesterol levels were measured. The mean serum LDL of 10ml/kg grass juice fed normal rats was decreased by 11.64% than that of the laboratory diet fed control group (P